2021
DOI: 10.1002/jms.4782
|View full text |Cite
|
Sign up to set email alerts
|

A multiple‐method comparative study using GC–MS, AMDIS and in‐house‐built software for the detection and identification of “unknown” volatile organic compounds in breath

Abstract: The human respiratory system is a highly complex matrix that exhales many volatile organic compounds (VOCs). Breath‐exhaled VOCs are often “unknowns” and possess low concentrations, which make their analysis, peak digging and data processing challenging. We report a new methodology, applied in a proof‐of‐concept experiment, for the detection of VOCs in breath. For this purpose, we developed and compared four complementary analysis methods based on solid‐phase microextraction and thermal desorption (TD) tubes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Prior studies have reported quantifiable differences in about two dozen VOCs between individuals with COVID-19 versus healthy individuals as well as individuals with other respiratory diseases. Particularly striking here are COVID-19-associated elevated concentrations of certain alcohols such as butanol and propanol or derivatives ( 33 , 35 , 37 , 38 ), aldehydes such as heptanal, octanal, and nonanal ( 33 , 34 , 36 ), as well as ketones such as acetone and butanone or derivatives ( 33 , 38 ). Other substances with reported increased concentrations are various alkanes, alkenes, further aldehydes, aromatic substances, and their derivatives ( 33 , 34 , 36 38 ).…”
Section: Disease- or Metabolism-derived Volatile Organic Compoundsmentioning
confidence: 90%
See 3 more Smart Citations
“…Prior studies have reported quantifiable differences in about two dozen VOCs between individuals with COVID-19 versus healthy individuals as well as individuals with other respiratory diseases. Particularly striking here are COVID-19-associated elevated concentrations of certain alcohols such as butanol and propanol or derivatives ( 33 , 35 , 37 , 38 ), aldehydes such as heptanal, octanal, and nonanal ( 33 , 34 , 36 ), as well as ketones such as acetone and butanone or derivatives ( 33 , 38 ). Other substances with reported increased concentrations are various alkanes, alkenes, further aldehydes, aromatic substances, and their derivatives ( 33 , 34 , 36 38 ).…”
Section: Disease- or Metabolism-derived Volatile Organic Compoundsmentioning
confidence: 90%
“…Particularly striking here are COVID-19-associated elevated concentrations of certain alcohols such as butanol and propanol or derivatives (33,35,37,38), aldehydes such as heptanal, octanal, and nonanal (33,34,36), as well as ketones such as acetone and butanone or derivatives (33,38). Other substances with reported increased concentrations are various alkanes, alkenes, further aldehydes, aromatic substances, and their derivatives (33,34,(36)(37)(38). Decreased VOC-concentrations in COVID-19-breath were shown for methanol (33) and -in contrast to Ruszkiewicz et al (33) -acetone (35).…”
Section: The Smell Of Covid-19mentioning
confidence: 90%
See 2 more Smart Citations
“…The peaks obtained by GC-MS can be identified by matching measured spectra with spectra in a reference library, which takes into consideration not only the mass and intensities of the ions obtained but also the chromatographic retention index (RI) of the compound of interest [ 14 ]. Hence, the use of GC-MS for targeted and non-targeted metabolic studies, especially for breathomics, is highly suitable and powerful [ 15 ]. In recent years, GC-HRMS has gained popularity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%